Limites e potencialidades da utilização de técnicas compensatórias no manejo de águas pluviais em áreas já urbanizadas - Lopes, Bruna Lamorea Veiga (2021)
With the growth of urban areas, the problems are result of waterproofing in the soil aggravated by the use of drainage techniques that do not adequately deal with issue. The called Compensatory Techniques (CT) appeared as an alternative to bring the cycleof urban rainwater closer to normal cycles. However, the use of CT is often associated with situations in which urbanization will still be carried out, disregaring previously occupied areas. In this sense, the objetive os this work was to evaluate the limits and potentialities of the application of CT in already urbanized areas. For this, variables were identified in the literature that should be considered for the choice and implementation of CT. New variables specifically related to already urbanized areas was added and the final systematization results in a set that can be used in this type of area. The set of variables was applied in differents urbanization situations in the microbasin of Strem of Servidão, in Araraquara-SP, in the order to assess the conditions of employment of CT. To have an order of magnitude of the effects of the CT, the pre-dimensioning of some alternatives was also done. The results indicated that the variables used can contribute to better define the use of CT in already urbanized areas, with consideration of some additional concerns, but with potential for application, which can be enhanced by the combination of different techniques. This, it was observed that there a potential for application, especially for mal-sized CT, and better results can be obtained with the combination o diferente techniques.